PENGARUH MOTIVASI, PENGGUNAAN TEKNOLOGI INFORMASI DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PERUMDA PASAR ARGHA NAYOTTAMA - KOMANG TRISNA SARI DEWI; I KOMANG GDE TRISNA PURWANTARA; I GUSTI MADE SUASTIKA (GANEC SWARA, 2023)
The purpose of this study was to determine the effect of motivation, use of technology information and job traning on employee performance at the Perumda Pasar Argha Nayottama of Buleleng Regency. The analytical technique used in this research is SPSS Version 21.0 for windows.The results of the study indicate that motivation have an effect on employee performance at Perumda Pasar Argha Nayottama Buleleng Regency. Use technology affects the performance of employees at Perumda Pasar Argha Nayotama of Buleleng Regency from the results of hypothesis testing with the T-Test test shows that use technology has a positive and significant effect on employee performance. Job traning has an effect on employee performance at Perumda Pasar Argha Nayottama of Buleleng Regency. From the results of hypothesis testing with the T-Test test,it shows that job traning has a positive and significant effect on employee performance. Based on the results of the calculation of the f-test, it was obtained that the F-count > F-table was equal to 117,991 > 3.11., this indicates that the variables of motivation, use technology  and job traning have an effect on employee performance with the level of significant 0.000 < 0.050.